2020
DOI: 10.1111/cts.12868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bardoxolone Methyl on Hepatic Enzymes in Patients with Type 2 Diabetes Mellitus and Stage 4 CKD

Abstract: In a multinational placebo‐controlled phase III clinical trial in 2,185 patients with type 2 diabetes mellitus and stage 4 chronic kidney disease, treatment with the Nrf2 activator bardoxolone methyl increased estimated glomerular filtration rate, a measure of kidney function, but also resulted in increases in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma glutamyl transferase. These increases in liver enzyme level(s) were maximal after 4 weeks of treatment and reversible, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…Exposure of liver cells to omaveloxolone or its analogue, bardoxolone methyl, results in concentration‐dependent increases in both ALT and AST mRNA levels 28 . Omaveloxolone also increases ALT and AST protein levels in cell lines derived from nonhepatic tissues, such as colon, skeletal muscle, and kidney, indicating that omaveloxolone regulates transcription of ALT and AST genes in multiple organs 28,29 . ALT and AST catalyze the reversible transfer of amino groups between alanine or aspartate, respectively, and α‐ketoglutarate to form pyruvate or oxaloacetate and glutamate 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of liver cells to omaveloxolone or its analogue, bardoxolone methyl, results in concentration‐dependent increases in both ALT and AST mRNA levels 28 . Omaveloxolone also increases ALT and AST protein levels in cell lines derived from nonhepatic tissues, such as colon, skeletal muscle, and kidney, indicating that omaveloxolone regulates transcription of ALT and AST genes in multiple organs 28,29 . ALT and AST catalyze the reversible transfer of amino groups between alanine or aspartate, respectively, and α‐ketoglutarate to form pyruvate or oxaloacetate and glutamate 31 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Omaveloxolone also increases ALT and AST protein levels in cell lines derived from nonhepatic tissues, such as colon, skeletal muscle, and kidney, indicating that omaveloxolone regulates transcription of ALT and AST genes in multiple organs. 28,29 ALT and AST catalyze the reversible transfer of amino groups between alanine or aspartate, respectively, and α-ketoglutarate to form pyruvate or oxaloacetate and glutamate. 31 Thus, these enzymes play key roles in metabolic processes, including the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…All other markers did not show significant changes between treatments, or within genotypes. An increase in serum levels of AST and ALT was also observed in patients treated with CDDO-Me 54 . In this study the increase in serum levels of transaminases was transient.…”
Section: Plasma Chemistry Profile In Vivomentioning
confidence: 77%
“…Bardoxolone methyl is an antioxidant inflammation modulator medication that activates the Nrf2 pathway and was designed to treat chronic kidney disease [152]. In a phase III trial of 2185 patients with stage 4 chronic kidney disease and type 2 diabetes, bardoxolone increased glomerular filtration rate but also lead to increases in AST/ALT and GGT.…”
Section: Miscellaneous Causes Of Dilimentioning
confidence: 99%
“…Enzyme elevations were maximal at week 4 and reversible, returning back to baseline after 48 weeks. No cases met Hy's law but two patients discontinued treatment after ALT rose >10× ULN [152]. The authors noted that preclinical animal and cell culture experiments suggested that the increases in ALT and AST seen with bardoxolone methyl appear to be related to its pharmacological activity, as it significantly induced the messenger RNA expression of ALT and AST isoforms in cultured cells.…”
Section: Miscellaneous Causes Of Dilimentioning
confidence: 99%